Implications of Nd isotopic mapping for crustal composition and metallogenesis in the Sanjiang orogenic belt (SW China) - Yuan, Lingling; Chai, Peng; Hou, Zengqian; Zheng, Yuanchuan; Quan, Haihui (Frontiers in Earth Science, 2023)
The Sanjiang orogenic belt in southwestern China and the southeastern Tibetan Plateau includes a variety of economically important metal deposits. Previous studies have focused on Lu‒Hf isotopic mapping to suggest the lithospheric architecture and mineralization. In this study, we provide the results of Nd isotopic mapping and compare them with the results of Hf isotopic mapping based on the similarity of Sm–Nd and Lu–Hf isotope systems, which indicate three juvenile domains with high εNd(t) and young Nd model ages within the Eastern Qiangtang-Simao terrane, while presenting negative εNd(t) values over the entire horizon. The very negative εNd(t) and old Nd model ages found in the Tengchong-Baoshan terrane and Changning-Menglian suture suggest that these terranes are old and might be reworked. The Nd isotopic mapping of the Sanjiang orogenic belt also suggests a relationship between different lithospheric architectures and the locations of distinct ore deposits. Porphyry-skarn Cu–Mo–(Au) deposits occur in the juvenile crust, which has relatively high εNd(t) (-3.3~5.1) and young TDM ages, whereas skarn and hydrothermal vein-type W–Sn deposits and Pb‒Zn‒Cu‒Ag deposits are located in the low-εNd(t) area.